2013
DOI: 10.21307/sjcapp-2014-005
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Difficulties among Children and Adolescents with Ethnic Danish, Immigrant, and Refugee Backgrounds

Abstract: Objective: This study investigated and compared the prevalence of psychological difficulties among Danish, immigrant, and refugee children. Methods: We enrolled 332 children between the ages of 8 and 18 years (148 Danish children, 81 immigrant children, and 67 children with refugee backgrounds), all from low-income areas of residence. The Health Behaviour in School-aged Children Symptoms Checklist, the Strengths and Difficulties Questionnaire, and the Revised Children's Anxiety and Depression Scale were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…A link between insecure attachment and both internalizing and externalizing problems has, however, been established, and thus, the complete lack of an association between insecure attachment and internalizing problems in the present study is inconsistent with both theoretical assumptions and previous research (Brumariu & Kerns, 2010;Lyons-Ruth, Easterbrooks, & Cibelli, 1997). Furthermore, a recent study comparing psychological difficulties among children and adolescents with ethnic Danish, immigrant, and refugee backgrounds employed the youth self-report version of the SDQ and this study concluded that refugee children were at a higher risk for psychological difficulties associated with both externalizing and internalizing than the two comparison groups (Leth, Niclasen, Ryding, Baroud, & Esbjørn, 2014). The tendency for traumatized refugee parents to underreport re-experiencing symptoms in their preschool age children was documented by Almqvist and Brandell-Forsberg (1997).…”
Section: Open Communicationcontrasting
confidence: 99%
“…A link between insecure attachment and both internalizing and externalizing problems has, however, been established, and thus, the complete lack of an association between insecure attachment and internalizing problems in the present study is inconsistent with both theoretical assumptions and previous research (Brumariu & Kerns, 2010;Lyons-Ruth, Easterbrooks, & Cibelli, 1997). Furthermore, a recent study comparing psychological difficulties among children and adolescents with ethnic Danish, immigrant, and refugee backgrounds employed the youth self-report version of the SDQ and this study concluded that refugee children were at a higher risk for psychological difficulties associated with both externalizing and internalizing than the two comparison groups (Leth, Niclasen, Ryding, Baroud, & Esbjørn, 2014). The tendency for traumatized refugee parents to underreport re-experiencing symptoms in their preschool age children was documented by Almqvist and Brandell-Forsberg (1997).…”
Section: Open Communicationcontrasting
confidence: 99%
“…Specifically, general mental health was worse27 48; adolescents catastrophised more that PFP-free counterparts46; and an active group employed different coping strategies 44. Other results suggestive of elevated scores on tests of psychological features were: high levels of fear avoidance in 26% of an adolescent cohort39; levels of anxiety/depression in Danish adolescents (12%–15%)46 above that reported in normative data for Danish school-aged children (8.8%)53; and a study from the UK38 reporting a greater prevalence of anxiety/depressive symptoms (26%) than that recorded for the general population by the Office of National Statistics (19%) 54…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, studies have found refugee children to be at higher risk of mental health difficulties compared to native and migrant children (Dalgaard, Todd, Daniel & Montgomery, 2016;Fazel & Stein, 2003;Leth, Niclasen, Ryding, Baroud & Esbjørn, 2014;Thommessen, Laghi, Cerrone, Baiocco and Todd, 2012). In England, Fazel and Stein (2003) found more than a quarter of the assessed refugee children to be at risk of psychological difficulties; a higher percentage than both migrant and native English participants.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to native children, refugee children also scored significantly higher on emotional difficulties, hyperactivity scores, peer problems as well as the total difficulties score. In Denmark the SDQ has similarly been used to compare the mental health of refugee-, migrant-and native Danish children (Leth et al, 2014), where refugee children were found to score significantly higher than native Danish children on the conduct disorder and the peer problems scale. These results indicate that refugee children may benefit from support initiatives, based on their specific needs, within schools.…”
Section: Introductionmentioning
confidence: 99%